THE ROLE OF COLLABORATION ON COMPANY INNOVATION PERFORMANCE IN INDONESIA - Musfirah Majid (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2021)
This study aims to determine the effect of cooperation with internal parties, suppliers, competitors, universities, government, consultants, R&D companies on the innovation performance of companies in Indonesia. This study used data of 927 respondents which were filtered into 136 data. The data used is the 2014 Indonesia Innovation Survey (IIS) for the period 2011-2013. The research data were processed using the Tobit regression method. The data is processed using STATA. The results of this study found that collaboration activities with internal parties, suppliers, and the government has a positive effect on company performance. Meanwhile, cooperation with competitors, universities, consultants and R&D companies does not significantly influence the innovation performance of companies in Indonesia.